Chronic intestinal failure in children - Krawinkel, Michael; Wessel, Lucas (Deutsches Ärzteblatt, 2012)
The term “chronic intestinal failure” (CIF) refers to the body’s inability to meet its energy and nutritional needs through the gastrointestinal tract (1). In pediatrics, a number of diseases of the gastrointestinal tract, both congenital and...
Gesehen am 05.09.2018